Evaluation of Gait Performance of a Hemipelvectomy Amputation Walking with a Canadian Prosthesis - M. T. Karimi; M. Kamali; H. Omar; Javid Mostmand (Case Reports in Orthopedics)
Background. Hemipelvectomy amputation is a surgical procedure in which lower limb and a portion of pelvic are removed. There are a few studies in the literature regarding the performance of subjects with hip disarticulation during walking. However, there is no study on gait analysis of hemipelvectomy subject. Therefore, the aim of this paper was to evaluate the gait and stability of subject with hemipelvectomy amputation. Case Description and Methods. A subject with hemipelvectomy amputation at right side was involved in this study. He used a Canadian prosthesis with single axis ankle joint, 3R21 knee joint, and 7E7 hip joint for more than 10 years. The kinetic and kinematic parameters were collected by a motion analysis system and a Kistler force platform. Findings and Outcomes. There was a significant difference between knee, hip, and ankle range of motions and their moments in the sound and prosthesis sides. In the other side, the stability of the subject in the anteroposterior direction seems to be better than that in the mediolateral direction. Conclusions. There was a significant asymmetry between the kinetic and kinematic performance of the sound and prosthesis sides, which may be due to lack of muscular power and alignment of prosthesis components.